MODEL KONSEPTUAL STRATEGI PENGEMBANGAN INDUSTRI KECIL MENENGAH BERBASIS SUMBER DAYA (STUDI KASUS PENGEMBANGAN IKM DI PANGALENGAN) - Asep Indra Sukendar Permana, Marimin, dan Gendut Suprayitno (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
ABSTRACT Small Medium Enterprises (SME’s) sector has an important role for regional economy, beside their complex problems. Competitive advantage of SME’s sector should be constructed in accordance with resilient character to be competitive. This research aimed to determine development priority areas of SME’s and resilient entrepreneurs of prime commodity and to construct a conceptual model of SME’s development strategy. The method used was Location Quotient (LQ), normal distribution, skalogram analysis, Bayes, Analytical Hierarchy Process (AHP), exponential comparison method (ECM), Value Chain Analysis (VCA), Valuable, Rare, Imitability and Organization (VRIO) analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE) and integration of Strengths, Weaknesses, Opportunities and Threats (I’SWOT) analysis with Interpretative Structural Modeling (ISM). Based on calculation results with Bayes method, Pangalengan had highest potential of local resources, so it was selected as the priority area for SME’s development. Referring to calculation results of ECM, Pangalengan had four prime commodities in agriculture selected the commodity resilient SME’s was snack foods processing (Pia Kawitan cakes). Determination of resilient SME’s serves as a reference for developing a small micro industrial sector, which was described in the form of conceptual model of SME’s development strategy. This research processing results showed that strategy position supported turn around strategy, which was located in quadrant III. SME’s development conceptual model consist of six groups, namely objective, criteria, actor, strategy supporter, strategy inhibitor and strategy alternative.Keywords: competitiveness strategy development, SME’s resilience, resources view